2019
DOI: 10.1016/j.vhri.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Economic Cost of Severe Acute Respiratory Infection Associated to Influenza in Colombian Children: A Single Setting Analysis

Abstract: Background: Influenza is considered a leading public health problem because its large economic burden of disease worldwide, especially in low-and middle-income countries, such as Colombia. Objective: We aimed to estimate the economic costs of influenzaconfirmed patients in a pediatric hospital in Cartagena, Colombia. Methods: We conducted a retrospective costing analysis. We estimated the direct (direct medical and out-of-pocket expenditures) and indirect costs for influenza-confirmed severe acute respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
1
11
2
Order By: Relevance
“…Cost estimations and differences across analyses are associated with some cost drivers as length of stay (LOS), comorbidities, and proportion of inpatients requiring Intensive Care Unit (ICU). The overall median LOS per patient in our study was 7 days (95% CI 4-12 days), similar to that reported in China (6 days) [32], but lower than that estimated in Colombian children (9 days; 95% CI, 6.3-11.5) [31]. The hospital LOS was greater in the elderly (7.5 days), but this estimation was less than other research (14 [32] and 17 [4] days).…”
Section: Plos Onesupporting
confidence: 85%
See 2 more Smart Citations
“…Cost estimations and differences across analyses are associated with some cost drivers as length of stay (LOS), comorbidities, and proportion of inpatients requiring Intensive Care Unit (ICU). The overall median LOS per patient in our study was 7 days (95% CI 4-12 days), similar to that reported in China (6 days) [32], but lower than that estimated in Colombian children (9 days; 95% CI, 6.3-11.5) [31]. The hospital LOS was greater in the elderly (7.5 days), but this estimation was less than other research (14 [32] and 17 [4] days).…”
Section: Plos Onesupporting
confidence: 85%
“…Some estimations have been performed for influenza vaccine cost-effectiveness analysis in extreme ages (< 2 years and > 65 years) from bottom-up costing in all-cause pneumonia inpatients, but without information reported of cost per case [30]. More recently, a SARI cost analysis in pediatric patients diagnosed by PCR and viral culture from a hospital in Cartagena reported a total direct medical cost (excluding OOPE and indirect costs) greater than us by 45% (I$ 2,523; IQR I$ 1,228-4,810), however the OOPE was 75% higher in our estimation, compared with the I$ 85 (IQR I$ 55-120) of Salcedo et al They also included a loss productivity evaluation ($ 152; IQR I$ 76-247) [31]. Differences between results could be explained by heterogeneity in sample sizes (44 vs 227 patients included), age structure (only children in Cartagena), and inclusion of contributive regimen population in our estimation.…”
Section: Plos Onecontrasting
confidence: 70%
See 1 more Smart Citation
“…Hospitalizing a COVID-19 case in the United States has been calculated at $14 366, 17 remarkably superior than our estimation. Other studies in Colombia have assessed the costs of hospitalization for infectious diseases such as influenza, 18 valuing median costs in the general ward for severe acute respiratory infection of $484 (2020 values) and in the ICU of $3044 (2020 values), 18 costs significantly lower than those described in our study.…”
Section: Discussionmentioning
confidence: 47%
“…The hospital admission rate to children's hospital between the years 2010 to 2018 increased between the months of October to December, with a higher percentage of cases in the months of November and December, which reveals that the "real peak" in our population begins 3-4 months after the end of the vaccination day (6 weeks after started in June of each year), which raises the need for a second vaccination campaign. In the meantime, it is important to continue vaccination against influenza as proposed by our Costa Rican health authorities, as this strategy decreases not only the burden of influenza disease, complications, hospitalization rates and deaths in children from Latin America (Sánchez-Ramos et al, 2017), but also, the associated economic costs of severe influenza infections (Salcedo-Mejía et al, 2019).…”
Section: Discussionmentioning
confidence: 99%